End user and implementer experiences of mHealth technologies for noncommunicable chronic disease management in young adults: a qualitative systematic review protocol - Slater, Helen; Briggs, Andrew; Stinson, J.; Campbell, J. (The University of Adelaide, 2017)
The objective of this review is to systematically identify, review and synthesize relevant qualitative research on end user and implementer experiences of mobile health (mHealth) technologies developed for noncommunicable chronic disease management in young adults. "End users" are defined as young people aged 15-24 years, and "implementers" are defined as health service providers, clinicians, policy makers and administrators.The two key questions we wish to systematically explore from identified relevant qualitative studies or studies with qualitative components are.